2013
DOI: 10.1159/000350445
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Pulmonary Hypertension in Interstitial Lung Disease by Ventilation and Perfusion Defects Measured by Cardiopulmonary Exercise Testing

Abstract: Background: Pulmonary hypertension (PH) is common in interstitial lung disease (ILD). Since cardiopulmonary exercise testing (CPET) is useful in understanding the pathophysiology of respiratory disorders and can distinguish between ventilation and perfusion (V/Q) defects, it may have a role in the detection of PH in ILD. We evaluated whether CPET can detect PH through analysis of V/Q defects in ILD. Objectives: We aimed to use CPET to determine if there are changes in the ventilation and the activity pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
(23 reference statements)
2
20
1
Order By: Relevance
“…In the present study, even though mean group DLCO was lower in ILD+PVD compared with ILD−PVD, this difference was not statistically significant. In line with previous reports [19,21], the presence of pulmonary hypertension did not correlate with the severity of the restrictive ventilatory defect or the degree of desaturation on exertion. Age, sex, BMI and radiographic findings were also similar between ILD+PVD and ILD−PVD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, even though mean group DLCO was lower in ILD+PVD compared with ILD−PVD, this difference was not statistically significant. In line with previous reports [19,21], the presence of pulmonary hypertension did not correlate with the severity of the restrictive ventilatory defect or the degree of desaturation on exertion. Age, sex, BMI and radiographic findings were also similar between ILD+PVD and ILD−PVD.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have been able to show a relationship between reduced DLCO and increased prevalence of pulmonary hypertension in patients with ILD [10,[18][19][20]. In the present study, even though mean group DLCO was lower in ILD+PVD compared with ILD−PVD, this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, CPET has proved to be useful in distinguishing between ILD patients with and without pulmonary hypertension. In the retrospective study of ARMSTRONG et al [71], ILD patients with pulmonary hypertension demonstrated significantly lower end-tidal carbon dioxide tension PETCO 2 and mixed expired carbon dioxide pressure (PECO 2 ) during exercise with a distinctive activity pattern for PECO 2 /PETCO 2 . DEGANI-COSTA et al [72] aimed to determine the functional significance of abnormal pulmonary arterial pressure (PAP) responses to exercise in 27 ILD patients and 11 age-matched controls using invasive cardiopulmonary exercise testing.…”
Section: The Role Of Cardiopulmonary Exercise Test In Ildsmentioning
confidence: 99%
“…Dumitrescu et al [22] studied parameters of cardiopulmonary exercise testing (CPET) in patients with scleroderma and found that a high V E /V CO 2 ratio and decreasing end-tidal partial pressure of CO 2 at anaerobic threshold (PET CO 2 ) identifies the presence of pulmonary vasculopathy. Armstrong et al [23] showed that CPET can help to detect PH in patients with interstitial lung disease.…”
Section: Introductionmentioning
confidence: 99%